2015
DOI: 10.1080/02786826.2015.1020997
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Penetration Through High-Efficiency Filter Media Typically Used for Aerosol Sampling

Abstract: We have developed a new, fully controlled filter testing device and have used it to measure size-resolved penetration through a typically used filtration media for (but not only) atmospheric aerosol sampling. Twenty membrane and fiber filter pieces (mixed cellulose ester filters, polytetrafluoroethylene filters, quartz fiber filters, glass fiber filters, and polycarbonate filters) of various manufacturers and filter codes were examined. High variability in the penetration curve shapes, most penetrating particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
(14 reference statements)
2
17
0
Order By: Relevance
“…The minimum collection efficiency, which is also referred to as the most penetrating particle size (MPPS), is obtained for the 100-300 nm size range. However, some studies showed that the MPPS for QFF may peak around 60 nm and are possibly < 100 nm for other fibrous media (Brochot et al, 2019;Zíková et al, 2015). While this measured values are mostly influenced by both the flow velocity in the sampling line and the pressure drop at the surface of the filter, our flow conditions are close to those used in the work of Zíková et al (2015).…”
Section: Sample Collectionsupporting
confidence: 51%
See 2 more Smart Citations
“…The minimum collection efficiency, which is also referred to as the most penetrating particle size (MPPS), is obtained for the 100-300 nm size range. However, some studies showed that the MPPS for QFF may peak around 60 nm and are possibly < 100 nm for other fibrous media (Brochot et al, 2019;Zíková et al, 2015). While this measured values are mostly influenced by both the flow velocity in the sampling line and the pressure drop at the surface of the filter, our flow conditions are close to those used in the work of Zíková et al (2015).…”
Section: Sample Collectionsupporting
confidence: 51%
“…CC BY 4.0 License. efficient in capturing combustion emissions and they have a stable penetration curve among other filters when a range of physical parameters are varying in the sampling line (Zíková et al, 2015). From a theoretical point of view, it is very difficult to predict the collection efficiency of QFF for particles within the nanometer size domain, as generated in our combustion conditions (e.g.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Assumptions of particle phase state are invalid. For instance, the organic constituents may not be ideally mixed (Robinson et al, 2015;Zuend and Seinfeld, 2012). Also, several types of ambient biogenic SOA particles have been shown to be not liquid, at least at certain humidity ranges, but to rather adopt an amorphous semisolid (i.e., glassy) state (Virtanen et al, 2010;Pajunoja et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The desorbed plume propagates normally from the sample surface in between the extraction plates of the ToF-MS. The molecules from the desorbed plume are then ionized by either a resonant two-photon ionization R2PI (Haefliger and Zenobi, 1998;Mihesan et al, 2006;Zimmermann et al, 2001) process at λ i = 266 nm (4 ns width pulsed UV laser, Continuum Powerlite, 1 mJ pulse −1 ) or a single-photon ionization (SPI) process at λ i = 157 nm (5 ns width pulsed vacuum ultraviolet (VUV) excimer laser, Coherent ExciStar XS 200) or λ i = 118 nm (in-house built coherent nanosecond source). The ninth harmonic of the Nd:YAG laser (λ i = 118.2 nm) was generated by tripling the 355 nm output of a Continuum Surelite pulsed laser in a Xe cell (Hilbig, 1982;Popovicheva et al, 2017).…”
Section: Two-step (Desorption-ionization) Laser Mass Spectrometrymentioning
confidence: 99%